Effect of fresh leaves extract of Acacia nilotica L. on the seed germination and seedling vigour of four common agricultural crops - Bharsakle, Lokesh; Singh, Charan; Dhanai, C.S. (Indian Journal of Agroforestry, 2020)
Decline in crop yields in agroforestry systems in recent years has been attributed to allelopathic effects. Acacia nilotica is a one of the main multipurpose tree species used in agroforestry systems and reported to have some allelopathic potential which might have been caused either by fallen leaves or plant leachate or root exudates. Hence, the present study was conducted to elucidate the allelopathic potential of different concentration of fresh leaf extract of Acacia nilotica on seed germination and shoot-root length of four common agricultural crops. A laboratory trial was conducted to assess allelopathic effect of four concentrations viz. 20%, 15%, 10% and 5% of aqueous extracts of fresh leaf of Acacia nilotica and a control (distilled water) on seed germination and soot-root elongation of maize (Zea mays), syabean (Glycine max), wheat (Triticum aestivum) and chickpea (Cicer arietinum). The aqueous extract of 20% concentration was prepared by soaking 200 g of leaves powder in 1000 ml distilled water for 24 hours at room temperature and from this extract, aqueous extracts of 5%, 10%, and 15% were prepared by dilution. The experiment was conducted in sterilized petri dishes. Leaf leachates of Acacia nilotica significantly decreased seed germination percentage in maize, wheat and chickpea at all concentrations (5%, 10%, 15% and 20% conc) but promoted seed germination percentage in soybean at lower concentrations (only 5%). It also decreased shoot-root length of maize, wheat and chickpea and increased shoot-root length of. It was found that Acacia nilotica had more inhibitory effect on maize, wheat and chickpea and promontory effect on soyabean.